Morphological Characterization and Physical Dormancy of Bauhinia winitii Seed: Living Collection of Purwodadi Botanic Garden - Lestari, Dewi Ayu; Firdiana, Elok Rifqi (Biosaintifika: Journal of Biology & Biology Education, 2021)
Bauhinia winitii Craib (Fabaceae, Caesalpinioideae) is a woody climber which is currently included in endangered species list. B. winitii seeds are orthodox seeds in which it has hard coat morphologically. Therefore, B. winitii seeds often undergo physical dormancy which can be broken through immersion in certain liquid media. This study aimed to characterize the morphology of B. winitii seeds and determine the pre-sowing treatment method to accelerate the seeds germination of B. winitii. External morphological characterization was carried out by observing the seeds quantitative and qualitative parameters. Characterization of seeds internal morphology was conducted using a digital microscope. Physical dormancy breaking was carried out by immersion in warm and cold water for 24 hours. Morphological characterization data were analyzed descriptively, while seed germination data were analyzed quantitatively by using one-way ANOVA followed by LSD test (with Â confidence level of 95%). B. winitii has pod-shaped fruits with 2-6 seeds per pod, the seeds are 1.36 cm x 1 cm in size, 0.47 cm thick and weighed 0.5 g, oblong to conical in shape, smooth and shine surface, with light to dark brown in color. Seeds immersion treatment in warm water could break the physical dormancy of B. winitii seeds thus 63% of the seeds were able to germinate and it was significantly different compared to control and cold water immersion treatment. Technical to germinate B. winitii seed can be known from pre-sowing treatment. This study can be used as a reference for seed identification and germination technical of B. winitii seed.